What Pinnipeds Have to Say about Human Speech, Music, and the Evolution of Rhythm - Ravignani, Andrea; Fitch, W. Tecumseh; Hanke, Frederike D.; Heinrich, Tamara; Hurgitsch, Bettina; Kotz, Sonja A.; Scharff, Constance; Stoeger, Angela S.; de Boer, Bart (Frontiers in Neuroscience, 2016)
Research on the evolution of human speech and music benefits from hypotheses and data generated in a number of disciplines. The purpose of this article is to illustrate the high relevance of pinniped research for the study of speech, musical rhythm, and their human origins, bridging current research with primates and birds. We briefly discuss speech, vocal learning and rhythm from an evolutionary, comparative perspective. We review the current state of knowledge on pinniped communication and behaviour relevant to the evolution of human speech and music, showing interesting parallels to hypotheses on rhythmic behaviour in early hominids. We suggest future research directions in terms of species to test and empirical data needed.